PRODUCTIVITY AND METABOLISM BY USING DIFFERENT ADDITIVES IN THE DIET SELEN CONTAIN BULLS - Приліпко, Т. М.; Захарчук, П. Б.; Гончар, В. І.; Косташ, В. Б. (Podilian Bulletin: Agriculture, Engineering, Economics, 2015)
The results of studies on the productive performance of bulls and digestibility of feed for selen contain using different additives in their diet. Found that different drugs selen contain essentially no effect on feed intake bullocks research groups. Each head controls group spent on average for dobu618 g of digestible protein abo100 grams per fodder unit. And 1 and 2 and the experimental group comprised those costs 617-619 g per 1 head abotezh100 g of 1 fodder unit. This average daily animal 1 st and 2 research groups prevailed over control respectively 67 grams; or 8.7% (P <0.05); 82 g; or 10.8% (P <0.001). It is noted that the increase of selenium in the diet positively affected the digestibility coefficients of nutrients in animal research groups: dry matter intake in the control group digested bulls at 67.8%; while the animal 1-2 th research groups 71.3 -72% which is 5.1% more than -6.1; digestibility of crude oil bulls in control 56.2% in research on 9;3-10;2% (P <0.05) more. At the highest digestibility coefficients of crude oil recorded in bychkiv2 nd experimental group that received a diet supplement selen contain "Devivit." MAR digestibility compared to control animals of the 1st experimental group difference was 5.5; 2nd pilot - 6.5%. In general; better digestibility of nutrients obtained in a group of animals fed a diet drug selen contain "Devivit."